Replacement of energy crops with bio-waste in existing anaerobic digestion plants: An energetic and environmental analysis. (1st June 2018) - Di Maria, Francesco; Sisani, Federico; Lasagni, Marzio; Borges, Marisa Soares; Gonzales, Thiago H.
Abstract: The energetic and environmental consequences of replacing energy crops (ECr) with bio-waste were analyzed by comparing two different scenarios. In the base scenario about 17, 500 Mg/year of ECr and about 30, 000 Mg/year of bio-waste were processed separately in an existing anaerobic digestion (AD) plant and composting plant, respectively. In the modified scenario the whole amount of bio-waste was used to replace the ECr as feedstock in the existing AD facility. The net amount of electrical energy recovered went from about 6700 MWh/year for the base scenario to about 9100 MWh/year for the modified one. From the environmental point of view the modified scenario was able to decrease both global warming and photochemical ozone formation potentials, whereas the base scenario had lower fresh water eutrophication potential and was able to avoid the consumption of resources. Both endpoint impact categories, human health and ecosystem quality, indicated that the modified scenario performed better than the base scenario. The uncertainty analysis confirmed qualitatively the results achieved.